THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF TWO STAY TWO STRAY AND MAKE A MATCH ON STUDENTS’ MATHEMATICS LEARNING OUTCOMES IN CLASS VIII OF SMP MUHAMMADIYAH BOARDING SCHOOL YOGYAKARTA - Diah Nur Octavia Sari; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2017)
Learning by discussion among the group has been less effective, which makes low the mathematic learning results. The research aims to determine there are differences in mathematics learning outcomes between using model cooperative learning type Two Stay Two Stray and cooperative learning type Make a Match. And compare the effectiveness of model cooperative learning type two stay two stray and make a match in the VIII grade of Junior High School student of Muhammadiyah Boarding School Yogyakarta in the even semester academic year 2015/2016. This study uses a posttest-only control design. There is three class in the population of this study, samples were taken from two classes with random sampling techniques to the class. Data collection was conducted with the test model. The instrument used questions related to the subject of surface area and volume of the pyramid. Before analyzing data, there is a prerequisite test that consists of a normality test and a homogeneous test. To test the hypothesis in this study, the test was used one party with a significant level of 5%. The results of research on the significant level of 5% and dk = 64 indicates that: there are difference in the results of students mathematics leaning using cooperative learning model TSTS, and using cooperative learning Make a Match type. This is indicated by the value and which mean and TSTS cooperative learning model is more effective than the cooperative learning model Make a Match type, against the mathematic learning student's results. This is indicated by the value and which mean .